2003
DOI: 10.1161/01.hyp.0000049621.85474.cf
|View full text |Cite
|
Sign up to set email alerts
|

Renal Sympathetic Nerve Responses to Tempol in Spontaneously Hypertensive Rats

Abstract: Recent studies have implicated a contribution of oxidative stress to the development of hypertension. Studies were performed to determine the effects of the superoxide dismutase (SOD) mimetic 4-hydroxy-2,2,6,6-tetramethylpiperidine-N-oxyl (Tempol) on vascular superoxide production and renal sympathetic nerve activity (RSNA) in anesthetized Wistar-Kyoto (WKY) rats and spontaneously hypertensive rats (SHR). Compared with WKY rats (n=6), SHR showed a doubled vascular superoxide production, which was normalized by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
119
3
3

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(132 citation statements)
references
References 29 publications
7
119
3
3
Order By: Relevance
“…Previous studies reported that intracerebroventricular infusion of tempol did not alter blood pressure in SHR. 13 Zanzinger et al, 17 however, demonstrated that chronic oxidative stress in the RVLM increases sympathetic nerve activity, suggesting that this site plays an important role in modulating sympathetic nerve activity by an increase in ROS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies reported that intracerebroventricular infusion of tempol did not alter blood pressure in SHR. 13 Zanzinger et al, 17 however, demonstrated that chronic oxidative stress in the RVLM increases sympathetic nerve activity, suggesting that this site plays an important role in modulating sympathetic nerve activity by an increase in ROS.…”
Section: Discussionmentioning
confidence: 99%
“…11 Furthermore, intravenous infusion of tempol decreases blood pressure, and these effects are mediated by the inhibition of renal sympathetic nerve activity. 12,13 Among the target organs of hypertensive vascular diseases, the brain is most affected by aging and oxidative stress. 14,15 The brain contains a high concentration of polyunsaturated fatty acids in its cell membranes.…”
mentioning
confidence: 99%
“…ET-1 was shown to be important in O 2 иϪ production in the sympathetic neurons of DOCAsalt hypertensive rats, and this was mediated by upregulation of ET (B) receptors (46). Renal sympathetic nerves respond to tempol by ameliorating elevation of high blood pressures in SHRs by decreasing oxidative stress (304). Longterm antioxidant treatment improves sympathetic functions and the ␤-adrenergic pathway in the SHRs (80).…”
Section: High Saltmentioning
confidence: 99%
“…1 4-Hydroxy 2,2,6,6,-tetramethyl piperidine 1-oxyl (tempol), a superoxide dismutase (SOD) mimetic, lowers blood pressure in normotensive and hypertensive rats by multiple mechanisms. [2][3][4][5] Acute tempol treatment of normotensive, DOCA-salt and spontaneously hypertensive rats (SHRs) inhibits sympathetic nerve activity and this effect is not prevented by nitric oxide synthase (NOS) inhibition. [2][3][4][5][6] Local application of tempol onto renal sympathetic nerves decreased nerve activity without changing blood pressure (BP) or heart rate (HR).…”
Section: S Uperoxide Anion (Omentioning
confidence: 99%